Pembuatan Biopelet dari Campuran Cangkang dan Daging Biji Karet Menggunakan Mesin Screw Oil Press - Mardiana Sari; Aminur Aminur; M. Agung Wibowo; Fikri Ramadhoni (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
The purpose of this research is to get the optimum condition of temperature and ideal ratio biopellet made from shell and kernel of rubber seed by using screw oil press machine according to Indonesian National Standards (SNI 8021-2014) which include heating value, ash content, moisture content, volatile matter, and density of biopellet. Comparison of the basic ingredients shell and kernel of rubber seed in this research include 80:20, 70:30, 60:40, 50:50, and 40:60 with varying temperature 200ᵒC and 150ᵒC. The results of the research it is known that the best composition of biopellet is a sample at temperature 200ᵒC, and ratio of shell and kernel of rubber seed 80:20 with calorific value of 5,083.4919 cal/g, moisture content of 4,00%, density 1.6322 gr/ cm3, ash content 1.9802%, volatile matter 77.1881%, and fixed carbon 16.8317%. The calorific value and the proximate analysis have fulfilled the SNI 8021:2014.